P6_6 Beginner Magic - Loch, Callum; Edkins, Troy; Woodcock, Nathaniel; Nicholls, Tristram (Physics Special Topics, 2022)
In many forms of media that include magic one of the earliest spells learnt creates water, be it as a flow or floating ball. This paper will calculate how much energy is required to perform this spell as well as discuss the environment required to produce this energy by using special relativity and the Stefan-Boltzman law for radiative transfer over a small circular face that connects the magic source to the world of the user. The Energy to create an orb of water with a radius of 5cm is 4.71238898 × 1016J this requires an temperature of the radiator to be between 22681040 ≈ 2.3 × 107K and 3207177 ≈ 3.2 × 106K depending on the area of the radiation source